High‐throughput quantum‐mechanics/molecular‐mechanics (ONIOM) macromolecular crystallographic refinement with PHENIX/DivCon: the impact of mixed Hamiltonian methods on ligand and protein structure. Issue 11 (2nd November 2018) - Borbulevych, Oleg; Martin, Roger I.; Westerhoff, Lance M.
Abstract : Quantum‐mechanics/molecular‐mechanics (ONIOM) X‐ray macromolecular refinement using the program DivCon integrated with PHENIX is reported. Abstract : Conventional macromolecular crystallographic refinement relies on often dubious stereochemical restraints, the preparation of which often requires human validation for unusual species, and on rudimentary energy functionals that are devoid of nonbonding effects owing to electrostatics, polarization, charge transfer or even hydrogen bonding. While this approach has served the crystallographic community for decades, as structure‐based drug design/discovery (SBDD) has grown in prominence it has become clear that these conventional methods are less rigorous than they need to be in order to produce properly predictive protein–ligand models, and that the human intervention that is required to successfully treat ligands and other unusual chemistries found in SBDD often precludes high‐throughput, automated refinement. Recently, plugins to the Python‐based Hierarchical ENvironment for Integrated Xtallography ( PHENIX ) crystallographic platform have been developed to augment conventional methods with the in situ use of quantum mechanics (QM) applied to ligand(s) along with the surrounding active site(s) at each step of refinement [Borbulevych et al. (2014), Acta Cryst D70, 1233–1247]. This method (Region‐QM) significantly increases the accuracy of the X‐ray refinement process, and this approach is now used, coupled with experimental density, to accurately determine protonation states, binding modes, ring‐flip states, water positions and so on. In the present work, this approach is expanded to include a more rigorous treatment of the entire structure, including the ligand(s), the associated active site(s) and the entire protein, using a fully automated, mixed quantum‐mechanics/molecular‐mechanics (QM/MM) Hamiltonian recently implemented in the DivCon package. This approach was validated through the automatic treatment of a population of 80 protein–ligand structures chosen from the Astex Diverse Set. Across the entire population, this method results in an average 3.5‐fold reduction in ligand strain and a 4.5‐fold improvement in MolProbity clashscore, as well as improvements in Ramachandran and rotamer outlier analyses. Overall, these results demonstrate that the use of a structure‐wide QM/MM Hamiltonian exhibits improvements in the local structural chemistry of the ligand similar to Region‐QM refinement but with significant improvements in the overall structure beyond the active site.